2014
DOI: 10.1021/am505873k
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Assembly of Tunable Nanoporous Materials from “Hairy” Silica Nanoparticles

Abstract: Membranes with 1-100 nm nanopores are widely used in water purification and in biotechnology, but are prone to blockage and fouling. Reversibly assembled nanoporous membranes may be advantageous due to recyclability, cleaning, and retentate recovery, as well as the ability to tune the pore size. We report the preparation and characterization of size-selective nanoporous membranes with controlled thickness, area, and pore size via reversible assembly of polymer brush-grafted ("hairy") silica nanoparticles. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…[58, 62-63, 76, 80, 127, 129] Another group demonstrated the suitability of the approach extended to silica spheres with the size of 390 nm to form free-standing membranes. [130] In another example, the cooperative effect from both the entanglements between PS chains, as well as strong vdW force between PS ligands and the Ag nanoparticles could facilitate the fabrication of the macroscopic 2D silver nanoassemblies that freely suspend over a wire loop larger than 1 cm. [131] Although the thickness of the entangled PS layers is only a few nanometers (3-6 nm) , they are mechanically robust, chemically stable, yet solvent and ion-permeable.…”
Section: Long Ligand Entanglementmentioning
confidence: 99%
“…[58, 62-63, 76, 80, 127, 129] Another group demonstrated the suitability of the approach extended to silica spheres with the size of 390 nm to form free-standing membranes. [130] In another example, the cooperative effect from both the entanglements between PS chains, as well as strong vdW force between PS ligands and the Ag nanoparticles could facilitate the fabrication of the macroscopic 2D silver nanoassemblies that freely suspend over a wire loop larger than 1 cm. [131] Although the thickness of the entangled PS layers is only a few nanometers (3-6 nm) , they are mechanically robust, chemically stable, yet solvent and ion-permeable.…”
Section: Long Ligand Entanglementmentioning
confidence: 99%
“…1.1579 . 1.1678 (7) Figure 11. Graph of the various models that can be used to estimate the particle size cut-off as a function of the silica particle size and volume fraction within the membrane.…”
Section: A Applications For Hairy Nanoparticle Membranesmentioning
confidence: 99%
“…If this equation is applied to cutoff experiments for different membranes [1,19], the overlap of the brushes can be estimated (assuming that the volume fraction is known to be ~ 0.64). Two sizes of spheres were experimentally tested: 280 nm and 460 nm silica spheres, with 24 nm and 30 nm length brushes, respectively.…”
Section: A Applications For Hairy Nanoparticle Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Most of these applications require control in the pore size, functional membrane surface, chemical and thermal stability. 34,35 It has been demonstrated that an amphiphilic phase separated copolymer of PS-b-PHEMA synthesized by ATRP has the ability to self-assemble into honeycomb patterned porous membranes. 36 From the perspective of functional bionanomaterial engineering, the PS-b-PHEMA copolymers are of signicant interest.…”
Section: Introductionmentioning
confidence: 99%